Comparison of Performance and Best Choice of Investment Instruments: A Study from Indonesia - Putri, Amelia Ivanka; Lutfillah, Novrida Qudsi; Djuharni, Darti (Universitas Bhayangkara Surabaya, 2024)
This research is based on the phenomenon of new investment trends by looking for which investment instrument is the best of four instruments, namely Antam Gold, LQ45 Shares, Reksa Dana, and Bitcoin Cryptocurrency. The research method used is a quantitative method with a comparative descriptive research type. The Sharpe, Treynor and Jensen index approaches are used to evaluate the performance of four investment instruments. the total sample size is 192 data. The results showed that LQ45 stocks produced the best performance during the Covid-19 pandemic. This condition is because LQ45 stocks can generate returns that are greater than the risk. The high return generated by LQ45 stocks even during the covid-19 pandemic was due to sectors that actually strengthened during the covid-19 pandemic. In addition, LQ45 stocks consist of stocks from the most liquid companies and have the largest market capitalisation so that these companies are resistant to crises.